ASSESSMENT OF THE ACTUAL NUTRITION OF CHILDREN AND ADOLESCENTS TAKING INTO ACCOUNT REGIONAL PECULIARITIES (E Conference Zone, 2022)
A hygienic assessment of the actual nutrition of children and adolescents is given, taking into account regional characteristics. Deviations in the structure of diets were noted